Knowledge, attitudes and adherence towards influenza and other vaccinations among healthcare workers at the University Hospital of Palermo, Italy, during the first COVID-19 pandemic season (2020/2021) - Costantino, C.; Bonaccorso, N.; Balsamo, F.; Belluzzo, M.; Carubia, A.; D'Azzo, L.; Grimaldi, F.; Sciortino, M.; Vitello, T.; Zagra, L.; Graziano, G.; Maida, C. M.; et al. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Increasing adherence to influenza vaccination among healthcare workers is a public health priority, stated that actually remains far below than international recommendations. During the 2020/2021 pandemic season, COVID-19 vaccines were not yet available until the end of December 2020, and influenza vaccines were the only one available to protect against seasonal respiratory diseases. The main objective of the present study was to assess knowledge, attitudes and adherence to influenza and other vaccinations recommended by the National Immunization Plan 2017-2021 for healthcare workers. Methods. Enrollment lasted from October and December 2020 at the vaccination unit of the University Hospital of Palermo. Data were collected through an anonymous and self-administered questionnaire, divided into 5 sections and 31 items. Results. Among 734 healthcare professionals that completed the survey, a significantly higher adherence to influenza vaccination was observed among healthcare workers that were more prone to receive COVID-19 vaccination (OR=4.02; 95% CI: 1.63-9.91). Moreover, higher influenza vaccination rates were observed among healthcare professionals that received influenza vaccination during previous 2019/2020 season (OR=15.3; 95% CI: 5.17-45.1) and that were favorable to the possible impact on increasing adherence of influenza mandatory vaccination (OR=4.88; 95% CI: 2.43-9.80). Conclusions. Propensity of healthcare workers to undergo vaccinations recommended in the National Immunization Plan increased during the first pandemic season. At the end of the vaccination season, flu vaccination coverage reached highest rates ever at the University Hospital of Palermo (around 60%), remaining anyway below the recommended minimum value of 75%. During next seasonal flu vaccination campaigns, it becomes essential to promote communication and information strategies to increase flu vaccination among healthcare workers, also focusing on co-administration with the anti-COVID-19 booster/seasonal doses.